QUALITY MEASUREMENT OF MOBILE BASED ACADEMIC INFORMATION SYSTEM AT VOCATIONAL HIGH SCHOOL - Glenn David Paulus Maramis (Indonesian Journal Of Civil Engineering Education, 2022)
The aim of this research is to ensure the quality of academic information systems to guarantee the functionality and to find out whether it meets the ISO 25010 quality standard. Testing was conducted using 4 of 8 characteristics of the ISO 25010, namely functional suitability, portability, usability, and performance efficiency. 490 respondents consisting of grade 1 to grade 3 students from various majors at one of state vocational high school in Manado were involved in collecting questionnaire data. Several measurement tools are used in this research, such as Page Speed tools, and also Yslow tools. For the instrument itself to analyze the usability is using USE Questionnaire. As the conclusion, the application system was meet the ISO/IEC 25010 standard with functional characteristic is 84.7% (very high), portability aspect is 100%, usability condition is 90%. For the performance efficiency aspect scores 93.7 and 0.907 for time speed parameters.